2021
DOI: 10.3389/fphar.2021.668708
|View full text |Cite
|
Sign up to set email alerts
|

Sinapic Acid Reduces Oxidative Stress and Pyroptosis via Inhibition of BRD4 in Alcoholic Liver Disease

Abstract: Alcoholic liver disease (ALD) is one of the main causes of death in chronic liver disease. Oxidative stress and pyroptosis are important factors leading to ALD. Bromodomain-containing protein 4 (BRD4) is a factor that we have confirmed to regulate ALD. As a phenolic acid compound, sinapic acid (SA) has significant effects in antioxidant, anti-inflammatory and liver protection. In this study, we explored whether SA regulates oxidative stress and pyroptosis through BRD4 to play a protective effect in ALD. Male C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 44 publications
1
12
0
1
Order By: Relevance
“…Consistent with our findings, SA has prevented isoproterenol-induced cardiac hypertrophy in rats [ 56 ]. No reports currently exist on the effect of SA on diabetes-induced renal and hepatic hypertrophy, but the parent group sinapic acid reversed renal hypertrophy in T1DM [ 139 ] and reduced relative hepatic weight in rats with chronic alcohol-induced liver injury and steatosis [ 140 ]. Thus, the mechanism of reducing hypertrophy could result in an improvement in dyslipidaemia, TGF-β1 inhibition, and anti-inflammatory and antioxidative effects.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with our findings, SA has prevented isoproterenol-induced cardiac hypertrophy in rats [ 56 ]. No reports currently exist on the effect of SA on diabetes-induced renal and hepatic hypertrophy, but the parent group sinapic acid reversed renal hypertrophy in T1DM [ 139 ] and reduced relative hepatic weight in rats with chronic alcohol-induced liver injury and steatosis [ 140 ]. Thus, the mechanism of reducing hypertrophy could result in an improvement in dyslipidaemia, TGF-β1 inhibition, and anti-inflammatory and antioxidative effects.…”
Section: Resultsmentioning
confidence: 99%
“…Sinapic acid could alleviate alcohol-induced oxidative stress by activating the Nrf2 signaling pathway to upregulate the expression of downstream key antioxidant proteins HO-1 and SOD. 39 The polyphenols extracted from Zizania latifolia could protect mice with acute alcoholism by increasing the level of antioxidant enzymes in serum. 40 In this study, ethanol could significantly promote the depletion of GSH, SOD, and CAT in AML-12 cells, while promoting the accumulation of MDA and ROS, indicating that the antioxidant defense system of AML-12 cells was disrupted.…”
Section: ■ Discussionmentioning
confidence: 99%
“…In previous studies, dietary polyphenols were found to have biological activities to maintain the body’s redox homeostasis. Sinapic acid could alleviate alcohol-induced oxidative stress by activating the Nrf2 signaling pathway to upregulate the expression of downstream key antioxidant proteins HO-1 and SOD . The polyphenols extracted from Zizania latifolia could protect mice with acute alcoholism by increasing the level of antioxidant enzymes in serum .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Brd4 appears to modulate the activation of different forms of inflammasome in response to distinct stimuli and the detailed molecular mechanisms merit further investigation (Fig. 4) [15,110,112,[116][117][118][119].…”
Section: Brd4 and Pyroptosismentioning
confidence: 99%